The Tragedy of the European Union : Disintegration or Revival?. - Soros, George (PublicAffairs, 2014)
The European Union could soon be a thing of the past. Xenophobia is rampant and commonly reflected in elections across the continent. Great Britain may hold a referendum on whether to abandon the union altogether. Spurred by anti-EU sentiments due to the euro crisis, national interests conflict with a shared vision for the future of Europe. Is it too late to preserve the union that generated unprecedented peace for more than half a century?This is no mere academic question with limited importance for America and the rest of the world. In the past decade, the EU has declined from a unified glob.